Pelatihan Pembuatan Bakso Rendah Lemak dan Berprotein pada Kader PKK di Cempaka 12 Kelurahan Mawar Kota Banjarmasin - Inayah, Husnul Khatimatun; Netty, Netty; Noorhidayah, Noorhidayah; Anggraeni, Septi; Octaviana, Elsi Setiandari Lely; Widyarni, Ari (Jurnal Abdimas Kesehatan (JAK), 2025)
Wrong diet is one of the risk factors that increase cardiovascular disease in the life phase of 45 to 60 years old which is characterized by the emergence of chronic diseases such as hypertension, type 2 diabetes, obesity and heart disease. At this stage of age, a low-fat and high-protein diet is essential for maintaining health, as low fat can prevent cardiovascular disease and protein consumption helps maintain muscle mass as well as improve the body's metabolism. The lack of information and awareness about pre-elderly health checks, especially the problem of excess fat in the blood that can cause cardiovascular disease is still a problem for PKK Cadre mothers in Cempaka 12, Banjarmasin City. The purpose of the Community Service Implementation (PkM) is to increase knowledge and provide skills in making low-fat and high-protein meatballs to PKK Cadre women in Cempaka 12, Banjarmasin City. The method of this activity consists of several stages, including: preparation, namely survey of the location of the activity, preparation of tools and materials, preparing the material to be delivered, pretest, counseling with lectures and discussions, posttest and demonstration and the target of the participants of the activity is 20 PKK women of Cempaka 12 Village. The PkM activity was held on August 13, 2025 at the house of the PKK Cadre Chairman. The results of the training showed a difference in the average knowledge score before and after the training, where the results of the pretest showed that the average of 10 questions was only able to answer between 3-4 questions correctly and the results of the posttest showed a significant increase with an average score of 9.4. It is hoped that after being given training, PKK cadres will contribute to increasing public knowledge about the consumption of animal and plant protein sources in daily life. Increasing the activeness of the role of Cadres in the implementation of Germas and periodic public health monitoring in the Cempaka 12 environment, Banjarmasin City.